The Structure and Elasticity of CaO3 Under High Pressure by First-Principles Simulation - Wang, Hanyu; Liu, Lei; Yang, Longxing; Sun, Fengxia; Yi, Li; Liu, Hong (Frontiers in Earth Science, 2022)
The structure, electrical properties, elasticity, and anisotropy of the newly discovered mantle mineral, CaO3, are obtained under 10–50 GPa by first-principles simulation to understand their relations with the composition and structure of the mantle transition zone. Crystal structure and phonon frequencies under 0–50 GPa indicate that CaO3 can exist stably under 10–50 GPa. Here, the band gap of CaO3 is 2.32–2.77 under the explored pressure and indicates its semiconductor property. The Mulliken population analysis shows that the Ca–O bond is an ionic bond, and O–O bond is a covalent bond, and the strength of the O–O bond is higher than that of the Ca–O bond. The density, bulk modulus, and shear modulus of CaO3 increase with increasing pressure. The compressional wave velocity (Vp) and shear wave velocity (Vs) of CaO3 increase with increasing pressure. The seismic wave velocity of CaO3 is smaller than that of the Preliminary Reference Earth Model (PREM) and common mantle transition zone minerals, and it is a very exceptional low seismic wave velocity phase. The anisotropies of Vs are 36.47, 26.41, 23.79, and 18.96%, and the anisotropies of Vp are 18.37, 13.91, 12.75, and 10.64% under 15, 25, 35, and 50 GPa, respectively. Those seismic velocity anisotropies are larger than those of the mantle transition zone’s main component, so CaO3 may be an important source of seismic wave velocity anisotropy in the mantle transition zone. Our results provide new evidence for understanding the material composition and the source of anisotropy in the mantle transition zone.